Odpowiedź :
[tex]a) \: 4 - 6x - 9 = 8x + 5 \\ - 6x - 8x = 5 - 4 + 9 \\ - 14x = 10 \: \: | \div ( - 14) \\ x = - \frac{5}{7} [/tex]
[tex]b) \: - 6(x + 5) = 90 \\ - 6x - 30 = 90 \\ - 6x = 90 + 30 \\ - 6x = 120 \: \: | \div ( - 6) \\ x = - 20[/tex]
[tex]c) \: 3x + 12(x - 1) = 4(x - 2) \\ 3x + 12x - 12 = 4x - 8 \\ 15x - 12 = 4x - 8 \\ 15x - 4x = - 8 + 12 \\ 11x = 4 \: | \div 11 \\ x = \frac{4}{11} [/tex]
[tex]d) \: 4x - 6 = - 4 - (x + 3) \\ 4x - 6 = - 4 - x - 3 \\ 4x + x = - 3 - 4 + 6 \\ 5x = - 7 + 6 \\ 5x = - 1 \: \: | \div 5 \\ x = - \frac{1}{5} [/tex]
[tex]e) \: 2 + 2(x - 2) = 3(x - 3) \\ 2 + 2x - 4 = 3x - 9 \\ 2x - 3x = - 9 - 2 + 4 \\ - x = - 11 + 4 \\ - x = - 7 \: \: | \div ( - 1) \\ x = 7[/tex]